Restorative justice and practice in US education - Roth, Kenneth R.; Kumah-Abiwu, Felix; Ritter, Zachary S. (Palgrave Macmillan, 2025)
"This edited volume offers a comprehensive overview of the dual concepts of Restorative Justice as a legal remedy and Restorative Practice as a philosophy to reduce harm and build resilient and just communities within social, cultural, and educational institutions. With contributions from leading practitioners and scholars, the book serves as a valuable resource for institutions seeking to center equity and reduce harm in multicultural learning spaces. Chapters combine insights into the origins and intent of Restorative Justice and Practice, showcase some of their early applications in higher education settings and beyond, and highlight their potential for promoting peace and building community on campuses across the country." --